1999
DOI: 10.1165/ajrcmb.21.2.3691
|View full text |Cite
|
Sign up to set email alerts
|

Forkhead Transcription Factor HFH-4 Expression Is Temporally Related to Ciliogenesis

Abstract: Members of the forkhead/winged-helix family of transcription factors are expressed in tissue-specific patterns and play critical roles in development and cell differentiation. The expression of forkhead family member hepatocyte nuclear factor-3/forkhead homologue 4 (HFH-4) has been localized by RNA-blot analysis and in situ hybridization to the proximal airway of the lung (trachea, bronchi, and bronchioles) with onset at mouse embryonic day (E) 14.5 and is present in the choroid plexus, ependymal cells, oviduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
123
0
4

Year Published

2004
2004
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(145 citation statements)
references
References 50 publications
18
123
0
4
Order By: Relevance
“…E16.5 was the first time that we detected, by immunohistochemistry, the neuroendocrine cell marker CGRP (calcitonin gene-related peptide). It was also the first time, in agreement with other studies, when surface cilia were detected, using antibodies to ␤-tubulin (6,30). It was now possible to observe, as previously described in human embryonic lung samples, that some of the CGRP ϩ neuroendocrine bodies are surrounded by Scgb1a1 ϩ Clara precursors, whereas others are ringed by a mixture of ciliated and Clara precursor cells (31).…”
Section: Resultssupporting
confidence: 89%
“…E16.5 was the first time that we detected, by immunohistochemistry, the neuroendocrine cell marker CGRP (calcitonin gene-related peptide). It was also the first time, in agreement with other studies, when surface cilia were detected, using antibodies to ␤-tubulin (6,30). It was now possible to observe, as previously described in human embryonic lung samples, that some of the CGRP ϩ neuroendocrine bodies are surrounded by Scgb1a1 ϩ Clara precursors, whereas others are ringed by a mixture of ciliated and Clara precursor cells (31).…”
Section: Resultssupporting
confidence: 89%
“…However, different types of axonemes have been described at the teleost KV, namely 9ϩ0 cilia in medaka (Okada et al, 2005) and 9ϩ2 cilia in zebrafish (Kramer-Zucker et al, 2005). In mouse, only 9ϩ0 cilia were published at the PNC (Sulik et al, 1994;Nonaka et al, 1998), yet the knockout of Foxj1, a gene that selectively affects 9ϩ2 cilia, revealed laterality defects nevertheless (Blatt et al, 1999;Brody et al, 2000). Probably in all of these studies, a limited number of cilia was analyzed ultrastructurally in cross-sections, and likely the entire critical time period from the first appearance of cilia to the asymmetric induction of the Nodal signaling cascade was investigated in mouse and fish.…”
Section: Discussionmentioning
confidence: 99%
“…Two transcription factors involved in the control of ciliary gene expression were analyzed. In mouse, the Forkhead transcription factor Foxj1 (formerly known as HFH-4) is expressed in cells bearing motile rather than sensory cilia (Blatt et al, 1999;Brody et al, 2000). Interestingly, loss-of-function mutations resulted in absent airway cilia without affecting PNC ciliogenesis, yet LR axis formation was compromised (Brody et al, 2000).…”
Section: Ciliary Gene Expressionmentioning
confidence: 99%
“…The embryonic expression of Foxj3 is strikingly different from that of Foxj1, which is specific for ciliated cells, e.g., in the airways and the node (Chen et al, 1998;Blatt et al, 1999;Brody et al, 2000), further emphasizing the evolutionary distance between these two genes. The closest relative, Foxj2, is expressed in gonads and preimplantation embryos , but nothing has been published on its postimplantation embryonic expression.…”
Section: Embryonic Foxj3 Expressionmentioning
confidence: 93%